Analisis Blibliometrik Strategi Branding dalam Pemasaran di Rumah Sakit - Setiyawan, David Mei; Raffa, Muhammad; Rizqy, Fikri; Hafiyyan, Hubaib Hakam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the trends, interrelations, and research development concerning corporate communication in hospital branding strategies through a bibliometric approach. Data were retrieved from the Scopus database for the publication period 2021–2025 using a combination of keywords: “hospital branding,” “corporate communication,” “healthcare reputation,” and “artificial intelligence.” The analysis was conducted using VOSviewer software to map keyword co-occurrence, author collaboration (co-authorship), and density as well as temporal visualizations. The results reveal that corporate communication serves as a central node in hospital branding research, functioning to build reputation and public trust through the integration of strategic communication and digital technology. Furthermore, the findings indicate a growing trend toward the adoption of artificial intelligence and social media to enhance brand image and patient experience. This study contributes theoretically to the development of technology-based corporate communication concepts in healthcare and provides practical implications for strengthening hospital reputation in the digital era.